2009
DOI: 10.1128/aem.00949-09
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid-Based System for High-Level Gene Expression and Antisense Gene Knockdown in Bartonella henselae

Abstract: Six broad-host-range plasmid vectors were developed to study gene expression in Bartonella henselae. The vectors were used to express a ␤-galactosidase reporter gene in B. henselae and to generate antisense RNA for gene knockdown. When applied to ompR, a putative transcription response regulator of B. henselae, this antisense RNA gene knockdown strategy reduced bacterial invasion of human endothelial cells by over 60%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…Bacteria were either cultured on heart infusion agar (Remel, Lenexa, KS) supplemented with 1% bovine hemoglobin (Remel, Lenexa, KS) (also known as chocolate agar) or in Schneider’s insect medium (Sigma, St. Louis, MO) supplemented with 10% fetal bovine serum (GE Healthcare Life Sciences, Pittsburgh, PA) and incubated for 3–4 days at 37°C in the presence of 5% CO 2 [24]. The pNS2-derived expression vector, which has been shown previously to replicate in Bh [25], was used as a backbone for construction of promoter reporter plasmids and introduced into Bh via electroporation [21]. For bacterial strains carrying the pNS2 plasmids, 50 µg/ml of kanamycin was supplemented to select for bacteria colonies that harbor the plasmid.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteria were either cultured on heart infusion agar (Remel, Lenexa, KS) supplemented with 1% bovine hemoglobin (Remel, Lenexa, KS) (also known as chocolate agar) or in Schneider’s insect medium (Sigma, St. Louis, MO) supplemented with 10% fetal bovine serum (GE Healthcare Life Sciences, Pittsburgh, PA) and incubated for 3–4 days at 37°C in the presence of 5% CO 2 [24]. The pNS2-derived expression vector, which has been shown previously to replicate in Bh [25], was used as a backbone for construction of promoter reporter plasmids and introduced into Bh via electroporation [21]. For bacterial strains carrying the pNS2 plasmids, 50 µg/ml of kanamycin was supplemented to select for bacteria colonies that harbor the plasmid.…”
Section: Methodsmentioning
confidence: 99%
“…The lacZ reporter gene encoding the beta-galactosidase enzyme was previously ligated into the pNS2 plasmid downstream of the strong trc promoter [25]. The divergent nepR and phyR promoters were PCR amplified from Bh genomic DNA using specific primers (Table S1) and ligated into the pNS2 plasmid to replace the trc promoter at the Sal I and Bam HI restriction sites.…”
Section: Methodsmentioning
confidence: 99%
“…fied as the major regulatory factor for transcriptional osmotic regulation in E. coli (34,53). Furthermore, ompR was shown to be involved in the virulence and survival of Brucella melitensis during macrophage infection (59), and a recent study suggested the involvement of ompR in the ability of B. henselae to invade HEC (23). Gene cluster 2 thus seems to reflect the B. henselae response to the drastic change in environment encountered at the onset of the in vitro infection and may comprise factors important for the establishment of contact with the HEC.…”
Section: Discussionmentioning
confidence: 99%
“…Our experiments demonstrated that expression of NrnC from B. henselae can rescue the growth defect of strain UM341 in the absence of Atc (data not shown). We cloned nrnC of B. henselae into a vector that allowed low-level expression, pNS2Amp, and a vector that allowed high-level expression, pNS2Trc (Gillaspie et al, 2009). The gene was in the reverse orientation such that the antisense strand was transcribed.…”
Section: Nrnc Activity Is Important For Growth In B Henselaementioning
confidence: 99%